The Understanding and knowledge on the right of Khiyar (options) in the business transactions among Setia Alam’s residents / Nur Afrina Mohamad Aidil - Mohamad Aidil, Nur Afrina (2019)
This research is conducted for the academic paper project with the title, “The Understanding and Knowledge on The Right of Khiyar (Options) in the Business Transactions Among Setia Alam’s Residents.” Nowadays, khiyar often overlooked and underestimated since it seems not important for the Malaysian Muslims to know about it. The problems that arise from the transaction between seller and buyer increasingly worrying the researcher. Many of the sellers did not want to accept the complaints from the consumers since they assume that once the contract is done, so there are no responsibilities for them towards the consumers and commodity. Furthermore, the society confronted many difficulties to whom they should refer to make complaints about the redresses that they faced from the seller. Thus, the objectives of this research are, 1) to study the level of understanding and knowledge about the right of khiyar among the respondents, 2) to identify the challenges and problems faced by the respondents that obstruct them from performing khiyar and 3) to determine the best solutions and suggestions to strengthen the right of khiyar in the contract. This study used quantitative method and collected data through online survey that was distributed among Setia Alam’s residents. To achieved the three objectives, the survey was spread diligently through WhatsApp and collected 101 responses. It is found that majority of the respondents do know about the rights of khiyar.